Effect of potassium chlorate on fruit quality of 'do' longan - W. Kanaree (2018)
The effect of potassium chlorate on flowering and fruit quality of 'Do' longan was studied in CRD having four treatments (KClO30, 200, 500 and 800 g/tree by soil application) with three replications (one tree/replication). The results revealed that fruit quality, fruit size, seed size, exocarp color, fruit pole strength, fruit volume, total soluble solids, and fresh and dry weight between fruits from the treated and untreated trees were not significantly different (P = 0.05). However, KClO3at the concentration of 800 g/tree reduced seed germination percentage. For the study of sulphur dioxide (SO2) residue in longan fruits, mature longan fruits which were harvested from KClO3untreated (0 g/tree) and KClO3treated (400 g/tree) trees were fumigated with SO2(1 g S/kg fresh fruit weight) for 30 min. The result revealed that KClO3did not affect SO2absorption capacity of the longan fruits. © ISHS.